Gagasan Pembaharuan Pendidikan Islam Sayyid Ahmad Khan - Arif Wahyudi (Tarbiyah Departement collaboration with AMCA, 2015)
Generally, questions reform movement within Islam can be grouped into three variants, the West, and Nationalism. For the first group, one of the things that can restore the glory of the Muslims is a necessity to return to the Islamic shariah. As for the second group, the basic principles which can restore the glory of the Muslims is to make the progress of Western civilization as an example and a model. As for the third group, the weakness of the Muslims caused by the reluctance of Muslims to acknowledge the existence of a variety of changes and developments in their lives. Because it's one way to cure it is to eliminate the old institutions were deemed unnecessary because Islamic civilization to develop institutions that also have suffered a setback.